(untitled) (Bioagro, 2024)
Bacterial stem rot, caused by Dickeya zeae, is among the main bacterial diseases of sweet corn, and finding sources of resistance is important. The objective was to evaluate the reaction of sweet corn genotypes to Dickeya zeae. The experiment was carried out at the Federal University of Uberlândia, in an 11 x 2 factorial scheme with four replications and in a randomized block design. The treatments consisted of 10 sweet corn genotypes (L2P1, L2P11, L2P33, L2P37, L2P45, L3P27, L4P19, L5P3, L5P18, L5P42), belonging to the Plant Germplasm Bank of UFU, Campus Monte Carmelo, a common commercial hybrid susceptible to Dickeya zeae (AS1633), and two D. zeae isolates (UFU J23 and UFU H113). At 45 days after planting, inoculation was performed using the syringe method. Evaluations were performed at 4, 8, 12 and 16 days after inoculation, observing the size of the lesion. In addition, the incubation period, disease severity and area under the disease progress curve were determined. Analysis of variance was performed and means were compared using the Scott-Knott test. The onset of the disease occurred between 96 and 204 hours after inoculation. The L2P33 and L2P37 genotypes showed high values ​​of area under the disease progress curve and disease severity, regardless of the isolate. The genotypes were classified as moderately susceptible, with emphasis on the L2P11 genotype.